GAMBARAN SELF EFFICACY DAN PENGETAHUAN PADA KLIEN TUBERKULOSIS: Self Efficacy and Knowledge Description on Tuberculosis Clients - Muhammad Afif Hilmi Masyfahani; Titin Sukartini; Ririn Probowati (LPPM STIKES Pemkab Jombang, 2020)
ABSTRACT Background : Tuberculosis is a contagious disease that is spread throughout the world and is a public health problem due to high morbidity and mortality. Along with the increasing prevalence of Tuberculosis events. Objective: To determine the self efficacy picture and knowledge of Tuberculosis clients in Bangil General Hospital. Method: Descriptive research with cross sectional approach. The research sample of 70 respondents with purposive sampling which inclusion and exclusion criteria. The instrument uses a questionnaire. Results: The results showed that tuberculosis clients had good self efficacy as many as 41 people (58.6%),%), quite as many as 20 people (28.6%) and the rest had less self efficacy as many as 9 people (12.9%) . and have good knowledge as many as 36 people (51.4%). Tuberculosis clients also have good knowledge as many as 36 people (51.4%), quite as many as 24 people (34.3%) and the rest have less knowledge as many as 10 people (14.3%). Conclusion: Clients' beliefs about self-care management can increase and be able to generate enthusiasm to seek knowledge, positive attitudes and self-management skills to improve and the client's health behavior in general. Client knowledge by providing information and understanding through a module media to the Tuberculosis client regarding Tuberculosis disease so as to increase the client's knowledge regarding management of her care. Keywords: Self efficacy, Knowledge, Tuberculosis